Detail specification for multi-contact edge socket electrical connectors. Single or double sided, open ended, metal fixing flanges, guide key location, replaceable contacts, through-board solder or wire wrap terminations. Full assessment level. (15th February 1979) - British Standards Institution,
No abstract available